2007
DOI: 10.1093/ajcn/85.4.989
|View full text |Cite
|
Sign up to set email alerts
|

Is higher dairy consumption associated with lower body weight and fewer metabolic disturbances? The Hoorn Study

Abstract: Background: Dairy consumption has been postulated to reduce the risk of obesity and metabolic disturbances. Objective: The aim of this study was to evaluate the associations of dairy consumption with body weight and other components of the metabolic syndrome. Design: We used cross-sectional data for 2064 men and women aged 50 -75 y who participated in the Hoorn Study. The metabolic syndrome was defined according to the National Cholesterol Education Program Expert Panel. Dairy consumption was assessed by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
119
3
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(136 citation statements)
references
References 43 publications
10
119
3
4
Order By: Relevance
“…Likewise, in the Coronary Artery Risk Development in Young Adults study, Pereira et al [8] found that among individuals (aged 18-30 years) who were overweight at baseline, dairy consumption was inversely associated with the incidence of obesity, abnormal glucose homeostasis, dyslipidemia, and hypertension over the next 10 years. In contrast, findings from the Hoorn cohort found that higher dairy product intake was significantly associated with higher fasting glucose concentrations and lower diastolic BP, but not with body weight or other metabolic variables (ie, lipids, postload glucose, or insulin [36]. In the latter study, when different dairy products were distinguished, significant inverse associations were observed for dairy desserts, milk, and yogurt with systolic and diastolic BP, whereas cheese consumption was positively associated with BMI.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Likewise, in the Coronary Artery Risk Development in Young Adults study, Pereira et al [8] found that among individuals (aged 18-30 years) who were overweight at baseline, dairy consumption was inversely associated with the incidence of obesity, abnormal glucose homeostasis, dyslipidemia, and hypertension over the next 10 years. In contrast, findings from the Hoorn cohort found that higher dairy product intake was significantly associated with higher fasting glucose concentrations and lower diastolic BP, but not with body weight or other metabolic variables (ie, lipids, postload glucose, or insulin [36]. In the latter study, when different dairy products were distinguished, significant inverse associations were observed for dairy desserts, milk, and yogurt with systolic and diastolic BP, whereas cheese consumption was positively associated with BMI.…”
Section: Discussionmentioning
confidence: 60%
“…On the other hand, the preponderance of evidence, mostly in adults, indicates that milk intake is more likely to be associated with beneficial cardiometabolic outcomes [13], [39], [40] and [41]. Few studies have shown the beneficial effects of other dairy products [10], [36] and [42].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the magnitude of blood pressure reduction was of greater magnitude after the diet rich in low-fat dairy products compared with the fruit and vegetable-rich diet, which omitted dairy products altogether (119) . The findings from cross-sectional and prospective observational studies have shown an inverse association between consumption of dairy products, particularly low-fat varieties, and risk of hypertension (64,65,(120)(121)(122)(123)(124)(125)(126) . The recent results from the Framingham Heart Study Offspring Cohort (n 2636) also showed benefit from low/reduced fat dairy products (127) .…”
Section: Dairy Proteins and Blood Lipidsmentioning
confidence: 99%
“…Epidemiologic studies have supported the hypothesis that a dairy-rich diet is associated with lower fat accumulation, although prospective and intervention studies are not unanimous [1][2][3][4][5][6]. Our understanding of the mechanisms responsible for this association remains incomplete.…”
Section: Introductionmentioning
confidence: 99%